Our national work in Palestine - Belkind, Israel (Pinski-Massel Press, 1918)
The spiritual center in Palestine.--Lessons derived from the Jewish colonization in Palestine.--How to perpetuate the emancipation of the Jews in Russia.--Kiriath Sefer.